Analisis Produktivitas Tenaga Kerja Menggunakan Work Sampling Pada Pekerjaan Kolom Dalam Proyek Konstruksi - Masayu Rishaputri Yusuf; Arfan Utiarahman; Arfan Usman Sumaga (Transbahasa, 2025)
Labor productivity is a crucial factor in the completion of a construction project, especially in column work that requires high efficiency. This study aimed to analyze labor productivity using the work sampling method on the work of column reinforcement on the 1st floor in the construction project of the Inpatient Building of RSUD dr. Hasri Ainun Habibie, Gorontalo. This study employed a work sampling method with a productivity rating approach and was accompanied by a questionnaire to identify factors influencing labor productivity. The time obtained in the field contained three types of activities, including effective time, contribution time, and ineffective time. Meanwhile, the questionnaire comprised 5 variables and 24 indicators. The study findings disclosed that the average LUR value on the column reinforcement work on the 1st floor of 17 (seventeen) days of work was 84.40%. This value indicated that the level of productivity was classified as productive and satisfactory. Then, the LUR value from the top ranking was the first day with a value of 89.31%, and the last was the fourth day with a value of 69.27%. In accordance with the results of the questionnaire distribution, it was found that the factor causing the highest labor productivity was the age variable with a coefficient of 0.840, and the lowest ranking was the weather variable with a coefficient of 0.577.